Understanding the relationships between physiological and psychosocial stress, cortisol and cognition - James, Katharine Ann; Stromin, Juliet Ilena; Steenkamp, Nina; Combrinck, Marc Irwin (Frontiers in Endocrinology, 2023)
Stress is viewed as a state of real or perceived threat to homeostasis, the management of which involves the endocrine, nervous, and immune systems. These systems work independently and interactively as part of the stress response. The scientific stress literature, which spans both animal and human studies, contains heterogeneous findings about the effects of stress on the brain and the body. This review seeks to summarise and integrate literature on the relationships between these systems, examining particularly the roles of physiological and psychosocial stress, the stress hormone cortisol, as controlled by the hypothalamic-pituitary-adrenal (HPA) axis, and the effects of stress on cognitive functioning. Health conditions related to impaired HPA axis functioning and their associated neuropsychiatric symptoms will also be considered. Lastly, this review will provide suggestions of clinical applicability for endocrinologists who are uniquely placed to measure outcomes related to endocrine, nervous and immune system functioning and identify areas of intervention.